A system analysis to assess the effect of low-cost agricultural technologies on productivity, income and GHG emissions in mixed farming systems in southern Ethiopia. (February 2021) - Berhanu, Yonas; Angassa, Ayana; Aune, Jens B.
Abstract: This study assessed the effects of various low-cost climate-smart agricultural (CSA) technologies on farm productivity, farm income and greenhouse gas (GHG) emissions in smallholder farming systems in southern Ethiopia. On-farm trials were conducted at three study sites/districts (Ziway, Halaba and Loka-Abaya) during the 2015 and 2016 cropping seasons. The experiment compared five climate smart treatments against existing recommended practice. Three farms were selected at each site. Each farm hosted one full experimental repetition, thus functioning as an experimental block. The average data of the two seasons were taken from each farm and means were calculated per site and over the study sites as well. The on-farm trails were established to identify a CSA technology that can improve yields and economic returns, while simultaneously reduce GHG emissions at the farm level. Averaged over the three sites, a combined application of seed priming with micro-dosing (0.5 g of fertilizer per pocket) was identified as the best-fit technology in terms of farm productivity and farm income. Results show that this technology increased maize grain yield by up to 45% (compared to the recommended practice). A model CSA farm was then created using this technology which was compared with the performance of the farmers' current system (conventional farm). It generated surplus production of both grain (more than three times higher) and fodder. The CSA farm produced 84% of dry matter fodder (DM) requirements and 60% of livestock crude protein (CP) needs respectively, while the conventional farm produced 30% DM and 48% of CP needs. Furthermore, the CSA farm demonstrated reduced GHG emissions compared to the conventional farm which grows maize without the use of mineral fertilizers. Our estimates indicate that due to the establishment of multipurpose trees on the CSA farm, the total on-farm C stock was about 29 Mg ha −1, that is 24% higher than the conventional farm. In conclusion, we recommend the combined application of seed priming and micro-dosing as a strategy for improving economic returns and an approach to enhance the sustainability of maize-based mixed systems in southern Ethiopia. Planting multipurpose trees will give additional benefits in terms of fodder and carbon sequestration. Highlights: We examine effects of CSA approach on productivity, income and GHG emissions. A model CSA farm was created using the best-fit CSA technology. We compare the CSA farm with the conventional practice. The CSA farm improves food and feed security, and a household's economy. The CSA farm had better GHG balance (0.23 Mg) than the conventional farm (0.12 Mg).